Te pou: an indigenous framework to evaluate the inclusion of family voice in family violence homicide reviews - Roguski, Michael (Journal of family violence, 2024)
Purpose: Within this paper we evaluate the inclusion of the family voice in the domestic homicide review process. We use an Indigenous rubric (Te Pou) developed to ensure a culturally appropriate framework for conducting fatality reviews. We further draw on the creative potential of Indigenous knowledge systems, applying them alongside Western understandings of the engagement of family in homicide reviews, to seed new knowledge. This review has been undertaken early in the process of implementing family interviews to learn from current practices, seeking to improve them and, thereby, be better hosts for those invited to be part of a review. Methods: The process of including family input into the in-depth reviews of family violence homicide reviews, conducted between October 2019 and November 2021, was reviewed against the guidelines specified within Te Pou. Results: While there were strengths within the current process, the review established that further work is required to fully embed cultural understandings and processes within homicide reviews. Indeed, the current process and legislative framework in which it is based, works against relational obligations of reciprocity and a duty to care. Conclusions: Using indigenous frameworks and research methods, it is possible to determine how homicide review processes have the potential to embed trauma rather than providing an opportunity for critical reflection and healing. Repositioning homicide reviews will require a reconceptualization of the legislative framework and support system requirements for review panels.